2013
DOI: 10.1186/1471-2172-14-50
|View full text |Cite
|
Sign up to set email alerts
|

The IL-6 response to Chlamydia from primary reproductive epithelial cells is highly variable and may be involved in differential susceptibility to the immunopathological consequences of chlamydial infection

Abstract: BackgroundChlamydia trachomatis infection results in reproductive damage in some women. The process and factors involved in this immunopathology are not well understood. This study aimed to investigate the role of primary human cellular responses to chlamydial stress response proteases and chlamydial infection to further identify the immune processes involved in serious disease sequelae.ResultsLaboratory cell cultures and primary human reproductive epithelial cultures produced IL-6 in response to chlamydial st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
20
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 32 publications
(47 reference statements)
2
20
0
Order By: Relevance
“…This study also showed that the PBMC production of IL-13 in response to chlamydial EBs also correlated with a reduced risk of infection (67). Our own research has demonstrated IL-6 production from endometrial and endocervical primary ex vivo cultures from live infections with C. trachomatis (68).…”
Section: Immune Responses In Pbmc In Womensupporting
confidence: 63%
“…This study also showed that the PBMC production of IL-13 in response to chlamydial EBs also correlated with a reduced risk of infection (67). Our own research has demonstrated IL-6 production from endometrial and endocervical primary ex vivo cultures from live infections with C. trachomatis (68).…”
Section: Immune Responses In Pbmc In Womensupporting
confidence: 63%
“…We have recently established the regulation of an early event- ICAM-1 via murine microRNA-214 in Ct infected murine genital tract may contribute to late stage upper genital pathology in an IL-17A dependent manner (Arkatkar et al 2015). Additionally, palmitic acid induces TNF-α and IL-6 (Zhou et al 2013), cytokines demonstrated by us and others to contribute significantly to causation of upper genital pathology in Ct infected mice (Murthy et al 2011; Cunningham et al 2013). …”
Section: Discussionmentioning
confidence: 95%
“…Despite its significant impact on global human health, how and why serovariants infect specific cell types, different tissues, and cause distinct pathology remains largely unknown. The majority of studies evaluating the host innate immune response to C. trachomatis have focused on a single serovar and a single cell-type (Miyairi et al, 2006;Buckner et al, 2013;Cunningham et al, 2013;Giakoumelou et al, 2017). Most studies have used human cervical carcinoma epithelioid (HeLa), human laryngeal carcinoma (Hep2), or murine fibroblast cells to model Chlamydia infection (Rasmussen et al, 1997;Dessus-Babus et al, 2002;Cunningham et al, 2013) while others have focused on epithelial cells of the endocervix (Ibana et al, 2012;Buckner et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…The majority of studies evaluating the host innate immune response to C. trachomatis have focused on a single serovar and a single cell-type (Miyairi et al, 2006;Buckner et al, 2013;Cunningham et al, 2013;Giakoumelou et al, 2017). Most studies have used human cervical carcinoma epithelioid (HeLa), human laryngeal carcinoma (Hep2), or murine fibroblast cells to model Chlamydia infection (Rasmussen et al, 1997;Dessus-Babus et al, 2002;Cunningham et al, 2013) while others have focused on epithelial cells of the endocervix (Ibana et al, 2012;Buckner et al, 2013). While Chlamydia can infect and replicate in a plethora of cell types, recent studies have shown that cells derived from different anatomical sites support different levels of Chlamydia replication and inclusion development (Miyairi et al, 2006;Jolly et al, 2019).…”
Section: Introductionmentioning
confidence: 99%